How (un)important is penis size for women with heterosexual experience? - Štulhofer, Aleksandar (Array, 2006)
A brief report on a study carried out in 1998 on heterosexual adult women in four Croatian cities, describing the findings on reported (un)importance of penis size (length, girth, appearance).